Mindful eating questionnaired: eating control, emotional eating and conscious nutrition trio: Mindful Eating Eating Control, Emotional Eating, Conscious Nutrition - Köse, Gizem; Çıplak, Mustafa Ertuğrul (Progress in Nutrition, 2020)
Objective: Present study, it was aimed to determine the relationship between university students’ mindful eating according to their age, body mass index and gender, and also to find mindful eating and subscales correlations and relationships, especially between emotional eating. Methods: This cross-sectional study was conducted 400 randomly selected undergraduate students in a university in Turkey. Participants completed Mindful Eating (MEQ) questionnaire that included questions related to their eating discipline, mindfulness, eating control, disinhibition, etc. Results: In our study, participants were aged between 18-26 and 35.0% were female and 65.0% were male, the mean BMI (kg/m²) was 22.93±2.93. There were no significant difference between participants applied with national examination and taken the talent selection in any statistical assessment (p>0.05). Mean MEQ score was 3.14±0.44 and there was no statistically significant difference between males (3.14±0.45) and females (3.14±0.43) (p> 0.05).  Obese group was found to be having less MEQ scores than any other BMI classes and participants in normal weight group had the highest MEQ score (p